Change in mental health service utilization from pre- to post-COVID-19 period in the United States - Md Rezaul Kader; Mohammod Mahmudur Rahman; Piali Dey Bristi; Foyez Ahmmed (Heliyon)
Objectives: This study aimed to explore the change in mental health service utilization before and after the COVID-19 pandemic as well as determine the association of various sociodemographic characteristics and comorbidities on the utilization pattern. Methods: Data from the National Health Interview Survey (NHIS) 2019 and 2022 were explored in this study. Along with the univariate analysis, bivariate analysis was conducted using the Chi-square and Cochran-Armitage trend tests. Stepwise binary logistic regression was implemented to find the best-fitted model and examine the effects of different factors on mental healthcare utilization. We also conducted a subgroup analysis for the variables that showed heterogeneous changes in utilization from 2019 to 2022. Results: Analysis of a total of 53,856 complete cases showed that the percentage of mental healthcare utilization changed from 20% in 2019 to 23.31% in 2022. Logistic regression results showed that the odds of mental health service utilization in the post-COVID period is 1.41 times of the pre-COVID [95% CI odds ratio (OR) = (1.26, 1.58)]. Sex, age, race, education, income group, insurance coverage, birth country, marital status, limitations of social functioning, having a place for healthcare, symptoms and history of depression/anxiety, diabetes, and hypertension had significant effects on the odds of receiving mental healthcare. Subgroup analysis revealed that the utilization changed significantly from 2019 to 2022 for age group “18–34” [OR = 1.41, 95% CI = (1.26, 1.58)], “35–49” [OR = 1.35, 95% CI = (1.21, 1.50)], and “50–64” [OR = 1.12, 95% CI = (1.01, 1.24)], while for the age group “above 64” was not significant. Conclusion: Pre- and post-COVID periods were found to be significantly different in terms of the utilization of mental healthcare utilization. Changes in the utilization was also found to differ in terms of different age groups.